Innovating Destination Planning: The Role of Local Development in Sustainable Tourism - Papageorgiou, Konstantinos; Milioris, Konstantinos; Kikilia, Katerina (Journal of Tourism, Sustainability and Well-being, 2025)
As tourism continues to grow worldwide, traditional destination planning models have faced criticism for neglecting environmental sustainability, socio-cultural preservation, and equitable economic distribution. This article examines how sustainable local development can be integrated into destination planning, offering a more balanced approach that benefits both local communities and the tourism industry. Through a comprehensive literature review of studies published from 2014 onwards, the article explores key concepts such as community-based tourism, environmental conservation, and socio-cultural preservation. Case studies from the European Union, including Slovenia, the Azores, and the Balearic Islands, are used to illustrate successful applications of sustainable destination planning. The article also highlights the challenges faced in balancing growth and sustainability and provides policy recommendations for stakeholder collaboration, responsible tourism, and long-term development strategies. By rethinking destination planning through the lens of sustainable local development, this article offers insights for policymakers, researchers, and industry practitioners seeking to promote responsible and resilient tourism.